Tantangan Dakwah Melalui Media Sosial di Era Media Baru - Anggit Pamungkas; Umi Halwati (Program Studi Komunikasi Penyiaran Islam Universitas Sains Al-Qur'an Jawa Tengah di Wonosobo, 2023)
The Islamic values that are communicated through da'wah are values that can intersect with the times, and one of these times is the digital era. Entering the digital age is like diving into the roar of a flood of information; it can be disorienting and make it hard to make sense of the world around you. In today's digital age, da'wah needs to be flexible enough to meet the needs of a population increasingly interested in